Evaluation of the Xpert HCV Viral Load Finger-Stick Point-of-Care Assay. (9th March 2018) - Lamoury, Francois M J; Bajis, Sahar; Hajarizadeh, Behzad; Marshall, Alison D; Martinello, Marianne; Ivanova, Elena; Catlett, Beth; Mowat, Yasmin; Marks, Philippa; Amin, Janaki; Smith, Julie; Ezard, Nadine; et al.
Abstract : This study demonstrated 100% sensitivity and specificity of the Xpert HCV VL FS test compared to the Abbott RealTime HCV Viral Load assay. This assay can detect active infection from a finger-stick sample in 1 hour, allowing single-visit HCV diagnosis. Abstract: Point-of-care hepatitis C virus (HCV) RNA testing is advantageous, enabling diagnosis of active infection in a single visit. This study evaluated the sensitivity and specificity of the Xpert HCV Viral Load Finger-Stick assay (Xpert HCV VL FS) for HCV RNA detection (finger-stick) and the Xpert HCV Viral Load assay (plasma) compared with the Abbott RealTime HCV Viral Load assay by venepuncture. Plasma and finger-stick capillary whole-blood samples were collected from participants in an observational cohort in Australia. Of 223 participants enrolled, HCV RNA was detected in 40% of participants (85 of 210) with available Xpert HCV Viral Load testing. Participants receiving HCV therapy were excluded from subsequent analyses (n = 16). Sensitivity of the Xpert HCV Viral Load assay for HCV RNA quantification in plasma collected by venepuncture was 100.0% (95% confidence interval [CI] 96.9%–100.0%) and specificity was 100.0% (95% CI, 94.4%–100.0%). Sensitivity of the Xpert HCV VL FS assay for HCV RNA quantification in samples collected by finger-stick was 100.0% (95% CI, 93.9%–100.0%) and specificity was 100.0% (95% CI, 96.6%–100.0%). The Xpert HCV VL FS test can accurately detect active infection from a finger-stick sample in 1 hour allowing single-visit HCV diagnosis.